A pedagogy for ethical decision making - Ryan, Michael (2017)
We examine a pedagogy for ethical decision-making that bridges the academic and theoretical with a dynamic and practical approach. We consider how two perspectives of mindfulness contribute to a sustainable practice. First, students explore their inner selves to build and strengthen their self-awareness. Building self-awareness and examining values and beliefs aligns with mindfulness meditation as presented by Lampe and Engleman-Lampe (2012). Second, a cognitive approach is used to examine ethics in depth using theory. This perspective aligns with the construct proposed by Langer and Moldoveanu (2000). We build on these approaches by engaging the individual’s belief and values system with theoretical foundations. We encourage the students to employ academic rigor and self-awareness as a practical approach to business ethics. The method is an ongoing and dynamic process. Sustainability depends on maintaining an informed state through the pursuit of a mindful and vigilant approach to the cognitive and self-awareness perspectives.